Molecular insights into the Drosophila piRNA pathway via systematic ReLo protein interaction screening and structure prediction - Salgania, Harpreet Kaur; Metz, Jutta; Lingren, Eric; Bleischwitz, Christian; Hauser, David; Máté, Katalin Oliveras; Bollack, Daniel; Lahr, Felix; Bruckmann, Astrid; Garbelyanski, Asen; Jeske, Mandy (Nucleic acids research, 2025)
piRNA-bound PIWI proteins mediate the silencing of transposons at both the transcriptional and post-transcriptional levels, processes that are critical for genome integrity and fertility in animals. Although numerous additional proteins are known to be essential for piRNA biogenesis and function in Drosophila and other animals, their molecular and mechanistic functions remain largely unknown. To advance our molecular understanding of the Drosophila piRNA pathway, we used a cell culture-based protein-protein interaction assay called ReLo to perform a systematic pairwise interaction screen involving 22 factors operating in the cytoplasm, including PIWI proteins, Tudor domain-containing proteins (TDRDs), RNA helicases, and mitochondrial surface proteins. Through additional ReLo interaction testing and structural modeling using AlphaFold, we have characterized six protein complexes at the molecular and structural levels. Both results of this screen and our combined methodological approach will likely serve as a valuable resource for future investigations into the molecular mechanisms of the piRNA biogenesis and function.
Veröffentlicht: 14. Oktober 2025
Gesehen am 02.02.2026